Audience differentiation and advertising strategy on interactive television - Babić, Aleksandar (Sociološki pregled, 2023)
Starting from the assumption that Serbia is in arrears with the implementation of the concept of interactive television and the creation of new forms of advertising, the author studies the transformation patterns of media content consumption using a multi-strategy research method of the habits of the young audience. Combining survey and in-depth interview techniques with qualitative content analysis, the author concludes that traditional TV advertising in the digital environment multiplies in terms of content, which is especially noticeable in the sphere of marketing communications. Young people increasingly apply different media technologies, switching from one device to another or using them simultaneously. Based on the analysis of the behaviour of the student population in the consumption of today’s television in Serbia, we have created a model of interactive television as a multifunctional portal in the context of advertising messages.
Keywords: interactive television; advertising; television audience; digital marketing; youth/students; secondary screen